Like many others who have written to CTA, - Kobessa, Alphonse (Technical Centre for Agricultural and Rural Cooperation, 1997)
Alphonse N'Kobessa of the Forum des jeunes producteurs pour le développement, Brazzaville, Republic of Congo is interested in raising quail and has asked us for practical information. We have summarized below some of the points that should be...